2018
DOI: 10.1155/2018/1969108
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Heparin-Binding Protein and D-dimers in the Early Diagnosis of Spontaneous Bacterial Peritonitis

Abstract: Objectives Ascites and spontaneous bacterial peritonitis (SBP) are among the most important complications of decompensated liver cirrhosis. In clinical practice, new inflammation biomarkers are needed for the early diagnosis of SBP, as well-known biomarkers, such as C-reactive protein (CRP), procalcitonin (PCT), or peripheral blood white blood cell (WBC) count, lack the required specificity and sensitivity. The aim of the study was to evaluate the significance of heparin-binding protein (HBP) in comparison to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 23 publications
2
15
0
2
Order By: Relevance
“…The search for a non-invasive and readily available biomarker for unmistakable diagnosis of SBP in cirrhotic patients with ascites, is still under clinical trials [22,23,29,30,32,33]. The current work, to the best of our knowledge, is the first to characterize the use of indexed combined measurement of serum PCT, ESR, and CRP for this purpose, after exclusion of non-SBP bacterial infections.…”
Section: Discussionmentioning
confidence: 96%
“…The search for a non-invasive and readily available biomarker for unmistakable diagnosis of SBP in cirrhotic patients with ascites, is still under clinical trials [22,23,29,30,32,33]. The current work, to the best of our knowledge, is the first to characterize the use of indexed combined measurement of serum PCT, ESR, and CRP for this purpose, after exclusion of non-SBP bacterial infections.…”
Section: Discussionmentioning
confidence: 96%
“…These reasons prompted many researchers constantly looking for new markers capable of predicting periprosthetic infection. D-dimer is a biomarker of disseminated intravascular coagulation and also increases in inflammation, thrombosis, and neoplastic disorders [12]. D-dimer has been widely used in the diagnosis of infection and the evaluation of patients' prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…In the prospective study, Schwameis et al [30] found that within 3.5 hours of early bacteremia, rapidly elevated D-dimer level could identify bacteremia and assess the prognosis and mortality in advanced septic shock. A D-dimer cutoff value of 1500 ng/mL had high sensitivity (96.8%) and high NPV (92.9%) for detecting spontaneous bacterial peritonitis; thus, Mikula et al [12] considered that it was significantly better than other inflammatory markers (white blood cell, CRP, and procalcitonin). In addition, D-dimer is recommended as a key diagnostic marker for infectious diseases such as endocarditis and mycoplasma pneumonia [29,31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given this situation, there is an urgent demand for joint surgeons to look for diagnostic markers with e ciency, cheapness, and convenience [13]. D-dimer is a brin degradation product formed by brinolysis of brin clots, which re ects the state of blood coagulation and increases in systemic or local infections, thrombosis, and neoplastic diseases [14][15][16]. Based on this principle, Shahi et al And Li et al speculated that d-dimer in PJI patients might serve as a neoteric diagnostic biomarker [17,18].…”
Section: Introductionmentioning
confidence: 99%